The Judge’s Consideration In Granting The Application For Marriage Dispensation After The Enactment Of Law No. 16 2019 - Mohamad Nuralim Supu (Estudiante Law Journal, 2020)
This research aims to: (1) Discuss how the Law affects the increase of marriage dispensation in the Gorontalo Religious Court. (2) to find out what is the basis of the judge to grant the application for marriage dispensation after the enactment of Law No. 16 of 2019. This study uses a type of empirical juridical research with a qualitative descriptive approach with the method of collecting interview data of Gorontalo Religious Court Judges and analyzing marriage dispensation data in 2019 and 2020 Gorontalo Religious Court. While the method of processing data researchers through the stage of data examination, classification, analysis and conclusions. The results of the study that the Revision of Law No. 16 of 2019 to Marriage Law No. 1 of 1974 greatly influenced the increase in marriage dispensation cases in the Gorontalo Religious Court. Because of people's ignorance about the change in the Law and because of the many extramarital relationships that cause pregnancy.